Aplikasi DCIM dengan Metode Agile untuk Pengelolaan dan Tracing Aset Dinas KOMINFO Kota Tangerang - Deva Vanola; Muhammad Ridwan Na’im; Wafiqah Nur Azizah; Wasis Haryono (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Tangerang City has the highest number of applications in Indonesia, with a total of 222 public service and government management applications supported by an ISO 27001:2013-certified data center. This data center is managed by the ICT Infrastructure and Cryptography Division of the Tangerang City Communication and Informatics Office. However, the process of managing data center assets and infrastructure still relies on OnlyOffice Nextcloud. This approach creates challenges in reading and processing data into meaningful information, data inconsistency, and the inability to track data changes effectively. Moreover, policymakers face difficulties in identifying devices that have reached their end of life (EOL) or are over five years old. This method limits strategic data analysis needed to support decision-making. Therefore, a digital system is required to manage data in a structured and consistent manner, track data changes, and provide relevant information for policymakers. Such a system is expected to enhance operational efficiency and support high-quality digital transformation.